Anti-diabetic effects of Campomanesia xanthocarpa (Berg) leaf decoction - Anapaula Sommer Vinagre; Ângela Della'Santa Rubio Origuella Rönnau; Sabrina Francisco Pereira; Lídia Uliano da Silveira; Elenir de Fátima Wiilland; Edna Sayuri Suyenaga (Universidade de São Paulo, 2010)
The objective of this research was to identify the effects of 3-week treatment of normal and streptozotocin-induced diabetic rats using a leaf decoction of Campomanesia xanthocarpa Berg. (20 g/L) on physiological, biochemical and histological parameters. Streptozotocin (STZ, 70 mg/kg in citrate buffer, pH 4.5) was administered IP to induce experimental diabetes one week prior to the treatment. STZ caused typical diabetic symptoms: polydypsia, polyuria, polyphagia, hyperglycemia, hypertriglyceridemia and histopathological modifications in the pancreas, liver and kidney. The treatment of diabetic rats using the decoction decreased blood glucose levels, inhibited hepatic glycogen loss, and prevented potential histopathological alterations in the pancreas and kidneys. No differences were found between the control rats treated with the decoction and the control rats maintained on water only. In conclusion, these results suggest that C. xanthocarpa leaf decoction (20g/L) might be useful for diabetes mellitus management, but further pharmacological and toxicological studies are needed. O objetivo deste trabalho foi identificar os efeitos do tratamento com o decocto das folhas de Campomanesia xanthocarpa Berg. (20 g/L), durante 3 semanas, sobre parâmetros fisiológicos, bioquímicos e histológicos de ratos normais e diabéticos induzidos por estreptozotocina. O diabete melito foi induzido uma semana antes de iniciar o tratamento experimental, pela administração IP de estreptozotocina (STZ, 70 mg/kg em tampão citrato, pH 4.5). Os ratos tratados com STZ apresentaram sintomas típicos de diabete: polifagia, polidipsia, hiperglicemia, hipertrigliceridemia e alterações histopatológicas no pâncreas, fígado e rim. O tratamento dos ratos diabéticos com o decocto diminuiu os níveis de glicose sanguínea, inibiu a degradação do glicogênio hepático e preveniu possíveis alterações histopatológicas no pâncreas e no rim. Nos ratos controles tratados com o decocto não foram verificadas diferenças significativas em relação aos controles tratados com água. Em conclusão, os resultados sugerem que o tratamento com o decocto das folhas de C. xanthocarpa leaf decoction (20 g/L) possa ser útil para o manejo do diabete melito, porém estudos farmacológicos e toxicológicos ainda são necessários.